The action of corticosteroids on orthodontic tooth movement: a literature review - Luegya Amorim Henriques Knop; Ricardo Lima Shintcovsk; Luciana Borges Retamoso; Ana Maria Trindade Grégio; Orlando Tanaka (Dental Press Editora, 2012)
INTRODUCTION: Tooth movement is initially characterized by an acute sterile inflammation, followed by sequential multiple reactions in the periodontal ligament in response to biomechanical forces. Pharmacological agents such as corticosteroids may affect the course of orthodontic movement. Scientific studies show antagonistic actions of these drugs on bone resorption during tooth movement. OBJECTIVE: To review the literature about the effect of corticosteroids on orthodontic tooth movement. CONCLUSION: Patients should be questioned regarding the use of these drugs in the orthodontic practice and for those who use them, the orthodontic treatment should be differentiated, with longer intervals between visits and periodic X-rays due to the delay in bone formation observed in some scientific studies. INTRODUÇÃO: a movimentação dentária é caracterizada, inicialmente, por uma inflamação aguda estéril, seguida por reações múltiplas sequenciais no ligamento periodontal em resposta às forças biomecânicas. Agentes farmacológicos, como os corticosteroides, podem alterar o curso da movimentação ortodôntica. Os estudos científicos demonstram ações antagonistas dessas drogas sobre a reabsorção óssea durante a movimentação dentária. OBJETIVO: realizar revisão de literatura sobre a ação dos corticosteroides no movimento dentário ortodôntico. CONCLUSÃO: os pacientes devem ser questionados quanto ao uso dessas drogas na clínica ortodôntica e, para aqueles que fazem uso, o tratamento ortodôntico deve ser diferenciado, com intervalos maiores entre as consultas e solicitação periódica de radiografias devido ao atraso na neoformação óssea observado em alguns estudos científicos.